Cytotoxic Clerodane Diterpenoids from Casearia obliqua - Vieira Junior, Gerardo Magela [UNESP]; Goncalves, Tiago de Oliveira [UNESP]; Regasini, Luis O. [UNESP]; Pinheiro Ferreira, Paulo M.; Pessoa, Claudia do O.; Costa Lotufo, Leticia V.; Torres, Roseli Buzanelli; Boralle, Nivaldo [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Cavalheiro, Alberto José [UNESP] (Amer Chemical Soc, 2009)
A crude bioactive EtOH extract of the twigs of Casearia obliqua afforded two new clerodane diterpenes, caseobliquins A (1) and B (2). Additionally, bioactivity-directed fractionation on a bioactive hexane extract of the leaves from this species led. to the isolation of the known clerodane diterpenes rel-6 beta-hydroxyzuelanin-2 beta-benzoate and rel-2 alpha-hydroxyzuelanin-6 beta-benzoate (3 and 4) as a mixture and 2 beta-hydroxyzuelanin-6 beta-cinnamate (5). The structures of the new clerodanes 1 and 2 were established on the basis of their 1D and 2D NMR spectroscopic data, and the new compound I and the known substance 5 had their absolute configurations determined by circular dichroism spectroscopy. The cytotoxicity of several of the compounds isolated was evaluated against a small panel of human tumor cell lines.